The Friction between Religious Groups during the Pandemic and the Urge of Dialogue - Mubarak, Ahmad Ridha; Muchlashin, Anif; Prajuliyanto, Agung (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This paper discusses conflict between and within religions occurring during the pandemic. The government’s regulation on closing public spaces, including houses of worship, has led all religious groups to perform and to do their worship from home. However, it is oftentimes disobeyed; some rituals and worships are believed to require a number of people to get involved in, including Jumah prayer which belongs to Islamic tradition and Ibadah Minggu which belongs to Christianity. The result shows that conflict that leads to violence often occurs in the process of reinforcing the regulation where mostly the rule-breakers act as the offenders. Yet, in some occasions, the Islamic tradition is generally treated in an exclusive manner. This paper also examines the best strategy to resolve religious conflict and to build peace as well as to prevent such conflict to happen yet another time in the future – that is, through dialogue accompanied by religious rituals and symbols.